2020
DOI: 10.1111/jonm.13029
|View full text |Cite
|
Sign up to set email alerts
|

Translation and psychometric validation of the Chinese version of the Emotional Labour Scale for nurses

Abstract: Objective To translate and psychometrically validate the Emotional Labour Scale (ELS) for nurses in China. Background Emotional labour is an indispensable component of nursing practice. We currently lack a standard instrument to assess nurses' emotional labour that fits the nursing context in China. Method Using convenience sampling, 561 nurses were recruited from five tertiary comprehensive hospitals. Internal consistency reliability, test–retest reliability, split‐half reliability, face validity, content val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Furthermore, by better understanding emotional labor in nurses, nursing organizations can develop more-effective strategies to reduce job stress, increase job satisfaction, and reduce turnover intention. The Chinese version of the Emotional Labour Scale originally developed by Hong and Kim (2019) has also recently been developed and tested for validation (Ying et al, 2020). The data obtained using this scale may be useful in developing human resources strategies and management policies for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by better understanding emotional labor in nurses, nursing organizations can develop more-effective strategies to reduce job stress, increase job satisfaction, and reduce turnover intention. The Chinese version of the Emotional Labour Scale originally developed by Hong and Kim (2019) has also recently been developed and tested for validation (Ying et al, 2020). The data obtained using this scale may be useful in developing human resources strategies and management policies for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Content validity indices, such as the I‐CVI (0.89 ~ 1.00), indicating that the experts agreed that most items were relevant and appropriate to assess the objectives of the Chinese version of the Stressor Scale for Emergency Nurses. For criterion validity, the results of Pearson's correlation test showed that the Chinese version of the Stressor Scale for Emergency Nurses for nurses was significantly correlated with the NBS ( r = 0.456, p < 0.001), but the correlation was moderate by general standards (Yao et al, 2020 ). When it comes to reliability, Cronbach α coefficient of the the Chinese version of the Stressor Scale for Emergency Nurses total table was 0.971, slightly better than those of the original version.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses’ emotional labor was measured using the Emotional Labor Scale for Nurses, which was developed by Hong J et al [ 28 ]. The scale has been translated and validated among Chinese nurses by Ying Y [ 29 ]. This scale includes three dimensions, namely “emotional control effort in profession” (7 items, e.g., “I try to be kind to patients genuinely from my heart”), “patient-focused emotional suppression” (5 items, e.g., “I suppress my anger when patients’ words and behaviors are unfair”), and “emotional pretense by norms” (4 items, e.g., “I exaggerate expressions of interest in patients”).…”
Section: Methodsmentioning
confidence: 99%